Kommunikationsformen und Deliberationsdynamik Eine relationale Inhalts- und Sequenzanalyse politischer Online-Diskussionen auf Beteiligungsplattformen - Esau, Katharina (Politische Kommunikation und demokratische Öffentlichkeit, 2022)
This book is dedicated to the dynamics of public deliberation online. Based on a critical examination of the traditional concept of deliberation, it discusses narration, expressions of emotion and humour as deliberative forms of communication in addition to argumentation. In addition to classic counter-argumentation, it considers empathy, constructiveness, reflection and genuine questions to be components of deliberative reciprocity. Empirically, relational content analysis and sequence analysis of two online participation platforms are used to investigate to what extent different forms of communication influence subsequent traditional and inclusive deliberative reciprocity.